SrAlOCl:Bi3+@SiO2 phosphor with broad emission band and its effects on LED optical power and correlated color temperature - Ha Thanh Tung; Huu Phuc Dang; Hoang Thinh Nhan (Bulletin of Electrical Engineering and Informatics, 2023)
Sr3Al2O5Cl2:Bi3+ (SAlOCl:Bi3+)phosphor for broadband emission was made using a solid-state method. From the extensive spectroscopic analysis and theoretical computation, significant conclusions about the origin of the Bi3+ emission were drawn. For the Sr 3 and Sr 1 sites, respectively, the dipole-quadrupole and quadrupole-quadrupole interactions were responsible for the concentration quenching in SAlOCl:Bi3+. The resulting luminescence mechanism demonstrated that the crystallization of Bi3+ at the two sites is what causes the emission from each site. The warm white light emitting diodes (LED) models were built with a 380-nm ultraviolet (UV) chip, SAlOCl:Bi3+, and two other phosphors. Then, the color rendering indeces (CRI) and the correlated color temperature (CCT) were calculated. Particularly, the CRI values ranged from 84.3 to 86.2 under operating currents of 20–50 mA, respectively. The increasing SAlOCl:Bi3+ dosage also heightened particle density, resulting in higher scattering coefficients. High scattering results in improved color coordination (lower color variance). The CRI and luminous flux are reduced as the phosphor SAlOCl:Bi3+ concentration increases more than owing to color loss and energy loss by backscattering and re-absorption. Thus, it is advisable to consider SAlOCl:Bi3+ carefully before applying in production.